Kepemimpinan Transformasional dan Dinamika Kinerja Tim dalam Organisasi Permais - Syahdanu, Arya; Siregar, Syahrizal Saib; Syahputra, M. Aldi; Astuti, Rahayu Fuji; Bayu, Syahdan Ivander (MUDABBIR Journal Research and Education Studies, 2024)
Transformational leadership has been known as one of the effective leadership styles in improving team performance in organizations. This study aims to analyze transformational leadership and team performance dynamics in the Serdang Bedagai Islamic Student Association (PERMAIS) organization. This study uses a qualitative approach with a descriptive method. Data were collected through a Google Form-based survey distributed to members of the organization, as well as semi-structured interviews to deepen the findings. The results of the study indicate that transformational leadership has a positive impact on team performance, especially in creating motivation, innovation, and effective communication among team members. Leaders who apply a transformational approach can influence team members through a clear vision, inspiration, and individual attention, although there are several obstacles such as the lack of member involvement in the decision-making process. This study underlines the importance of transformational leadership training to improve team effectiveness in achieving organizational goals. In conclusion, the effective implementation of transformational leadership can improve team performance through better collaboration, open communication, and attention to the individual needs of team members. A participatory approach and a culture of innovation are also needed to maximize team potential in student organizations.